Some approaches to obtaining internal audit evidence for pharmaceutical quality systems - Karamavrova, Tetiana; Lebedynets, Vyacheslav (ScienceRise: Pharmaceutical Science, 2019)
The aim of the work is to analyse approaches and develop proposals for the selection of optimal methods for collecting evidence of internal audits of pharmaceutical quality systems. Materials and methods. The study was based on the materials of the current state legislative and regulatory framework, ISO 9000 series standards, sources of foreign and domestic scientific literature, as well as the results of our previous research. The following methods were used in the study: system-analytical, sociological survey, comparative analysis, structural-logical modelling. Results. According to the results of previous studies conducted on the basis of domestic pharmaceutical enterprises of various fields of activity, it was found that the main reason for the often insufficient effectiveness of internal audits is the low level of professionalism of auditors. At this stage of the study, an investigation of such an internal audit method as an interview was conducted, and approaches to its application were analysed. In particular, it was found that the interview method is used at domestic pharmaceutical enterprises as the main method of collecting audit evidence for their further assessment and interpretation. It was also proved that one of the key skills of the auditor is to pose the correct, appropriate questions for obtaining informative answers. An algorithm for posing audit questions was developed and tested, optimized to increase the completeness and meaningfulness of staff responses. Conclusions. The study allowed us to propose an interview technique that is effective for collecting audit evidence, which increases the effectiveness of the internal audit process by increasing the value of the information received from the position of managerial decision-making